John Steinbeck in Vietnam - unknown:::Creator::::::::::::
John Steinbeck sitting with provincial governor (on the far right, wearing a silk suit) and another man. This was the headquarters for the U.S. aid operation in the north of the country. The Plain of Jars was one of the least stable areas of the country. On the photo is a handwritten caption that reads, "North East Thailand 1967."